2022
DOI: 10.1021/acscatal.1c04880
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic Oxidation of 5-Hydroxymethylfurfural Coupled with 4-Nitrophenol Hydrogenation in a Water System

Abstract: Electrocatalytic conversion of biomass-derived 5-hydroxymethylfurfural (HMF) to value-added 2,5-furandicarboxylic acid (FDCA) is of great significance for sustainable chemical production. The key challenge is to establish an electrocatalytic system with a wide potential window, which can selectively oxidize HMF to FDCA without causing water oxidation. In this study, Cu foam decorated with Cu(OH) 2 (CF-Cu(OH) 2 ) was successfully fabricated as an efficient catalyst, and CuOOH active species generated by electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 59 publications
4
90
0
Order By: Relevance
“…According to the Cu 2p XPS spectra, the peaks at ≈934.0 and 953.8 eV are attributed to Cu 2p 3/2 and Cu 2p 1/2 characteristic peaks, and the other two peaks are related satellite peaks (Figure 1c). [ 11 ] The peak position of Cu 2p in the CuO–PdO composite shifted towards the high binding energy compared with that of pure CuO, confirming the existence of electronic interaction between the two substances. The electron at the interface transferred from CuO to PdO, making PdO species the electron‐rich center and CuO the electron‐deficient center.…”
Section: Resultsmentioning
confidence: 76%
“…According to the Cu 2p XPS spectra, the peaks at ≈934.0 and 953.8 eV are attributed to Cu 2p 3/2 and Cu 2p 1/2 characteristic peaks, and the other two peaks are related satellite peaks (Figure 1c). [ 11 ] The peak position of Cu 2p in the CuO–PdO composite shifted towards the high binding energy compared with that of pure CuO, confirming the existence of electronic interaction between the two substances. The electron at the interface transferred from CuO to PdO, making PdO species the electron‐rich center and CuO the electron‐deficient center.…”
Section: Resultsmentioning
confidence: 76%
“…The oxidation of HMF to FDCA involves three serial key steps: (1) oxidation of the hydroxyl or the formyl groups of HMF to give DFF of HMFCA, (2) oxidation of DFF or HMFCA to give FFCA, and (3) oxidation of FFCA to give FDCA (Figure c). The rate constant of these elemental reactions, denoted as k 1 –k 5 , respectively, can be determined by assuming each to be a first-order reaction with respect to its reactant …”
Section: Resultsmentioning
confidence: 99%
“…Xu’s group successfully constructed a CuO/CoOOH heterostructure to achieve the boosted activation of the oxygen evolution reaction (OER) . Additionally, several researchers have successively proposed that high-valence metal species and oxyhydroxides generated by electrochemical activation could effectively contribute to the electrocatalytic reactions. Therefore, it is feasible to introduce efficient active species on the surface of a catalyst through electrochemical activation to establish a sustainable electrocatalytic system . However, the evolution processes and characterization methods of active species resulting from the electrochemical reconstitution have not been systematically studied as far as we have known.…”
Section: Introductionmentioning
confidence: 99%
“…After stimulation with the oxidative/reductive potential, the CF–CuO/CeO 2 precursor can react with the alkaline electrolyte to form abundant in situ active sites. 2,5-Furandicarboxylic acid (FDCA) is the oxidation product of HMF (a biomass-derived platform molecule), which is a valuable intermediate chemical for the production of polymers, fine chemicals, and pharmaceuticals. Meanwhile, 4-aminophenol (4-AP), as the hydrogenation product of 4-nitrophenol (4-NP), is also an important intermediate in the synthesis of fine chemicals. , Taking account of both HMF oxidation and 4-NP hydrogenation involved a six-electron process, , HMF oxidation and 4-NP hydrogenation were selected as the model reactions for revealing the crucial role of the in situ electrochemical reconstitution of CF–CuO/CeO 2 . More importantly, a series of physical characterizations and electrochemical experiments systemically indicated that the electrochemically generated active species of Cu 3+ /Ce 4+ and Cu + /Ce 3+ are the oxidative-/reductive-activated intermediates, respectively.…”
Section: Introductionmentioning
confidence: 99%